2001
DOI: 10.2310/6650.2001.34091
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and Hemodialysis in Humans

Abstract: These data indicate that chronic HD inhibited MCADA activity and increased ADO plasma concentration. Both high ADO plasma concentration and low MCADA activity may be involved in dialysis-induced immune system failure and thereby favor infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 62 publications
(94 reference statements)
0
31
0
Order By: Relevance
“…6,7 Venous blood (3 mL) was withdrawn under vacuum together with a stop solution in Vacutainer tubes (Becton Dickinson). This method allowed blood samples to be mixed rapidly with 4 mL of stop solution, which prevents adenosine degradation and uptake.…”
Section: Adenosine Plasma Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Venous blood (3 mL) was withdrawn under vacuum together with a stop solution in Vacutainer tubes (Becton Dickinson). This method allowed blood samples to be mixed rapidly with 4 mL of stop solution, which prevents adenosine degradation and uptake.…”
Section: Adenosine Plasma Levelsmentioning
confidence: 99%
“…6,7 Briefly, a modular system with a UV detector was used. Lyophilized samples were dissolved in 1 mL of phosphate buffer (pH 4) and eluted with a methanol gradient on a Merck LIChrospher C18 column.…”
Section: Adenosine Plasma Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids were separated on a Zorbax Eclipse XDB-C8 column, 4. Measurement of Plasma Nucleotide Concentrations-Plasma levels of ATP, ADP, and adenosine were measured using minor adaptations of previously published procedures (35,36). In brief, plasma samples were collected directly into stop solution, deproteinated by extraction with perchloric acid, then neutralized by extraction with a mixture of tri-n-octylamine and Freon.…”
Section: Enpp2-tg and Enpp2mentioning
confidence: 99%
“…Plasma atrial natriuretic peptide levels have been reported to be similar in hypotensive and normotensive dialysis patients [15,16], but the possible role of this molecule in chronic hypotension in uremia is controversial [6]. In addition, it has been shown that plasma levels of adenosine, a strong hypotensive agent, are increased, while the activity of intracellular adenosine deaminase, the enzyme that metabolizes this agent, is reduced in HD patients, but not in predialysis or peritoneal dialysis patients [17]. However, the possible role of this agent in hypotension in dialysis patients has yet to be fully evaluated.…”
Section: Discussionmentioning
confidence: 99%